4-Methoxymethyl-2, 3, 5, 6-tetrafluorobenzyl alcohol as a urinary biomarker for monitoring of metofluthrin, a fluorine-containing pyrethroid, in exposed rats. (February 2015) - Yoshida, Toshiaki
Abstract Context: A fluorine-containing pyrethroid metofluthrin is widely used recently in mosquito repellents. Objective: The urinary excretion kinetics of its metabolites was evaluated in rats to establish an optimal biomarker for monitoring metofluthrin exposure of the general population. Methods and results: After metofluthrin had been administered intraperitoneally to rats, the urinary excretion kinetics of the major metofluthrin metabolites was evaluated by moment analysis. The urinary excretion amounts of 4-methoxymethyl-2, 3, 5, 6-tetrafluorobenzyl alcohol were estimated to be proportional to the absorption amounts over a wide exposure range. Conclusion: Urinary 4-methoxymethyl-2, 3, 5, 6-tetrafluorobenzyl alcohol was considered to be an optimal biomarker for metofluthrin exposure.